2011
DOI: 10.1007/s12043-011-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dust-ion-acoustic waves in a multi-ion plasma with trapped electrons

Abstract: A dusty multi-ion plasma system consisting of non-isothermal (trapped) electrons, Maxwellian (isothermal) light positive ions, warm heavy negative ions and extremely massive charge fluctuating stationary dust have been considered. The dust-ion-acoustic solitary and shock waves associated with negative ion dynamics, Maxwellian (isothermal) positive ions, trapped electrons and charge fluctuating stationary dust have been investigated by employing the reductive perturbation method. The basic features of such dust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…where Φ 0 = (15U 0 /8A) 2 and Δ = (16B/U 0 ) are, respectively, the height and thickness (normalized by λ Di ) of the DIA solitary waves moving with the speed U 0 . This result is coincided with some other theoretical predictions for vortex like distribution like (Duha et al 2011). Some numerical appreciations of our results have been obtained numerically by analyzing the height and the thickness of the solitary waves by using the general expressions for the coefficients A and B [i.e.…”
Section: Numerical Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…where Φ 0 = (15U 0 /8A) 2 and Δ = (16B/U 0 ) are, respectively, the height and thickness (normalized by λ Di ) of the DIA solitary waves moving with the speed U 0 . This result is coincided with some other theoretical predictions for vortex like distribution like (Duha et al 2011). Some numerical appreciations of our results have been obtained numerically by analyzing the height and the thickness of the solitary waves by using the general expressions for the coefficients A and B [i.e.…”
Section: Numerical Analysissupporting
confidence: 89%
“…The current equation for negative ion (viz. I n0 ) follows the vortex-like distribution (Duha et al 2011).…”
Section: Governing Equationsmentioning
confidence: 98%
“…Among the modified modes, the dust-ion-acoustic (DIA) waves (DIAWs), which theoretically proposed by Shukla and Silin [1] and experimentally confirmed by Barkan et al [2], has received much attention. Significant research efforts have been devoted in investigating the characteristics of DIAWs in the pair-ion DPM (PIDPM) [5], and degenerate DPM [5,6]. Misra [5] studied the nonlinear propagation of DIA shocks waves in a quantum PIDPM, and numerically discussed the stationary shock solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Misra [5] studied the nonlinear propagation of DIA shocks waves in a quantum PIDPM, and numerically discussed the stationary shock solutions. Duha et al [6] considered a Multi-ion DPM, and observed both the solitary and shocks structures. Sahu and Tribeche [7] reported the electrostatic dust-acoustic (DA) solitary and shock structures in DPM having non-thermal plasma species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation